Effect of Long-term Land Use Management Practices on Distribution of C and N Pools in Water Stable Aggregates in Alfisols - and R. Lal, K.K. Bandyopadhyay (Journal of the Indian Society of Soil Science, 2015)
Soil aggregates enhance carbon (C) sequestration by physically protecting it from the microbial activity. The position of soil organic carbon (SOC) in the aggregates and its chemical nature affects the rate of its decomposition. Thus, a study was conducted using soils of a 16-year-old tillage experiment and the adjoining forest on a Crosby silt loam soil at the Waterman Agricultural and Natural Resource Laboratory of the Ohio State University, Columbus, Ohio to assess the effect of different management practices on the aggregate size distribution, the C and N concentrations in the aggregates, and the C and N pools associated in these aggregates. The data showed that the forest and the cultivated soils were statistically at par with respect to the aggregate mass distribution. In comparison with the cultivated soil, the forest soil had significantly higher C and N concentrations in bulk soil (117 and 98.7%), water stable aggregates (WSA) (80.9 and 68.9%), particulate organic matter (POM) (118.3 and 94.5%) and the mineral associated organic matter (MAOM) (69.1 and 62%). It also contained higher C (59%) and N (53.5%) pools than the cultivated soil. However, there was no significant difference between the conventional tillage and no-till system with respect to the C and N concentrations in the bulk soil, WSA, POM, MAOM and the C and N pools. The aggregate mass and C and N concentrations in the WSA, POM and MAOM and the C and N pools associated with the large macro-aggregates were significantly higher than in the other aggregate fractions. Total N, C:N ratio, particulate organic C, particulate organic N, C:N ratio of POM, mineral associated C, mineral associated N and C:N ratio of the MAOM accounted for 99.9% variation in the total soil C.